2015
DOI: 10.3168/jds.2014-8674
|View full text |Cite
|
Sign up to set email alerts
|

The effects of a garlic oil chemical compound, propyl-propane thiosulfonate, on ruminal fermentation and fatty acid outflow in a dual-flow continuous culture system

Abstract: The ban on the use of antibiotics as growth promoters in animal feeds in the European Union has stimulated research on potential alternatives. Recently, propyl-propane thiosulfonate (PTSO), a stable organosulfurate compound of garlic, was purified. The objectives of the current study were to investigate the potential effects of PTSO on rumen microbial fermentation and to define effective doses. Two experiments were conducted using dual-flow continuous culture fermenters in 2 replicated periods. Each experiment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 40 publications
1
21
1
Order By: Relevance
“…Allium species, such as garlic and chives, contain various organosulfur compounds, such as ajoene, vinyldithiins, DADS, and DATS [3438]. In the present study, we focused on the effects of GO and CO on the hippocampus-dependent neurogenesis and memory formation in naïve mice.…”
Section: Discussionmentioning
confidence: 99%
“…Allium species, such as garlic and chives, contain various organosulfur compounds, such as ajoene, vinyldithiins, DADS, and DATS [3438]. In the present study, we focused on the effects of GO and CO on the hippocampus-dependent neurogenesis and memory formation in naïve mice.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, the mixture of cinnamaldehyde (0.18 g/d) and eugenol (0.09 g/d) proved to be useful as food additives in beef heifers fed high grain diets, by modifying the rumen microbial fermentation (Cardozo et al 2006). The effect of a garlic oil chemical compound, propyl-propane thiosulfonate (PTSO), in an effective dose between 50 a 100 mg/L modify ruminal fermentation in a direction consistent with higher propionate molar proportion (Foskolos et al 2015).…”
Section: Essential Oils and Antioxidantsmentioning
confidence: 99%
“…Allyl mercaptan, a compound present in garlic oil, has been shown to decrease linoleic and linolenic acid hydrogenation [46], but little else is known. Two recent continuous culture fermentor experiments showed that diallyl disulfide, a major component of garlic essential oil, and two other components, propyl-propane thiosulfonate and propyl-propane thiosulfinate, decreased the BH of C18:3c9c12c15, and, for the former two components, increased C18:1t11 and C18:1c9, and decreased C18:0 [11,47]. An in vivo study in goats reported a limited but significant increase in the proportion of linoleic and linolenic acids, and a decrease in the proportion of C18:0 in rumen contents [45].…”
Section: Garlic Oilmentioning
confidence: 99%